On Roger Pouivet’s Religious Exclusivism (Философия религии: аналитические исследования, 2021)
In the contemporary discussion of religious diversity, religious exclusivism is a minority theory but well defended by some leading philosophers of religion like Alvin Plantinga. Recently, in his article, The Right to Believe that Only One Religion is True, published recently in “Philosophy of Religion: Analytic Researches”, Roger Pouivet has defended a version of religious exclusivism based on the assumption of theological realism. In this article, I discuss Pouivet’s religious exclusivism with a dual purpose. On the one hand, accepting the premises of theological realism, I agree with Pouivet’s view that religious exclusivism is not a blatant expression of arrogance about religious diversity but a plausible theory that can be justified in the light of the contemporary debate on epistemology of religious disagreement. On the other hand, I sustain that theological realism supports religious exclusivism as well as religious inclusivism, but the latter is a more consistent theory, capable of avoiding the soteriological problems raised by the first. In this perspective, I suggest that religious inclusivism is properly supported by natural theology insofar as the latter relates to divine attributes which are common to various religious traditions. Accordingly, natural theology must not be reduced, like Pouivet thinks, to a philosophical theology that assumes the immediate rationality of religious beliefs, guaranteed by the way they are formed. On the contrary, I suggest that natural and philosophical theology can work together, in their distinction, to rationally justify theistic faith and the belief that only one religion is true. In the light of the aforesaid one can believe that the issue of the correlation between philosophical theology and natural theology has sound methodological significance in various contexts of studies in philosophy of religion.